2004
DOI: 10.1021/ma0350213
|View full text |Cite
|
Sign up to set email alerts
|

Young's Modulus of Polyelectrolyte Multilayers from Microcapsule Swelling

Abstract: We measure Young's modulus of a free polyelectrolyte multilayer film by studying osmotically induced swelling of polyelectrolyte multilayer microcapsules filled with the polyelectrolyte solution. Different filling techniques and core templates were used for the capsule preparation. Varying the concentration of the polyelectrolyte inside the capsule, its radius and the shell thickness yielded an estimate of an upper limit for Young's modulus of the order of 100 MPa. This corresponds to an elastomer and reflects… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
153
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(166 citation statements)
references
References 33 publications
12
153
1
Order By: Relevance
“…These values (1 − 100 MPa), therefore, give the lowest limit for Young's modulus of polyelectrolyte multilayers. However, our results strongly support the conclusions of the recent swelling experiment [7], which has given a slightly larger, but of the same order of magnitude, value for E. We have argued [7], that the osmotically induced swelling measurements give the upper limit for Young's modulus. Therefore, taking together, these two types of experiment provide the range of possible values for Young's modulus of a PSS/PAH multilayer.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These values (1 − 100 MPa), therefore, give the lowest limit for Young's modulus of polyelectrolyte multilayers. However, our results strongly support the conclusions of the recent swelling experiment [7], which has given a slightly larger, but of the same order of magnitude, value for E. We have argued [7], that the osmotically induced swelling measurements give the upper limit for Young's modulus. Therefore, taking together, these two types of experiment provide the range of possible values for Young's modulus of a PSS/PAH multilayer.…”
Section: Discussionsupporting
confidence: 91%
“…If the capsule is highly permeable for the solvent (water) the capsule wall bends and a cup-like shape is formed. The second method is based on studying the swelling of microcapsules filled with the solution of a strong polyelectrolyte [7]. The * Corresponding author: vinograd@mpip-mainz.mpg.de third attempt involves measuring the deformation of microcapsules under applied load using atomic force microscope (AFM) [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…For practical applications, understanding the shell permeability and mechanical properties of the PMCs is of importance. The latter can be studied by osmotically induced buckling [889], by osmotic swelling [890] or by direct probing with the AFM.…”
Section: Mechanical Properties Of Microcapsulesmentioning
confidence: 99%
“…Typical examples of such shells are vesicles and liposomes with ionic channels, 1,2 various types of micro-and nanocapsules, [3][4][5][6] cell 7,8 and bacterial [9][10][11] membranes, viral capsids. 12,13 Such shells in a contact with a polyelectrolyte solution have been employed for measuring elastic 5,14,15 and elasto-plastic 16 modulus of the shell's material and for selective encapsulation. [17][18][19] Recent studies have shown that mechanical properties of semi-permeable capsules filled with polyelectrolytes, their aggregation and and sedimentation stability are strongly influenced by ionic Donnan equilibria between the container interior and the surrounding solution.…”
Section: Introductionmentioning
confidence: 99%